Slavery in John Chrysostom’s homilies on the Pauline epistles and Hebrews : a cultural-historical analysis - Stander, Hennie (Hendrik Frederik), 1953- (University of Pretoria, 2013)
Thesis (DLitt)--University of Pretoria, 2012.